2012
DOI: 10.2478/v10012-012-0012-8
|View full text |Cite
|
Sign up to set email alerts
|

Conceptual Design and Performance Analysis of an Exhaust Gas Waste Heat Recovery System for a 10000TEU Container Ship

Abstract: According to operation characteristics of the main engine 9K98ME-C7, a combined turbines-exhaust gas waste heat recovery system is proposed to recover waste heat and increase system energy efficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 4 publications
(4 reference statements)
1
19
0
Order By: Relevance
“…In spite of the lower temperature of the exhaust gas, steam-based Rankine cycles have also been proposed for application on two-stroke engines. Ma et al evaluated the part-load peformance of a single-pressure design (Ma et al, 2012). Dimopoulos et al proposed the thermo-economic optimisation of a steam-based WHR system for a containership powered by a two-stroke engine (Dimopoulos et al, 2011(Dimopoulos et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…In spite of the lower temperature of the exhaust gas, steam-based Rankine cycles have also been proposed for application on two-stroke engines. Ma et al evaluated the part-load peformance of a single-pressure design (Ma et al, 2012). Dimopoulos et al proposed the thermo-economic optimisation of a steam-based WHR system for a containership powered by a two-stroke engine (Dimopoulos et al, 2011(Dimopoulos et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Ma et al proposed and evaluated a singlepressure system, both in design conditions and at part-load (Ma et al, 2012). Ma et al proposed and evaluated a singlepressure system, both in design conditions and at part-load (Ma et al, 2012).…”
Section: The Application Of Organic Rankine Cycles For Waste Heat Recmentioning
confidence: 99%
“…According to MAN Diesel & Turbo [2], the combined power turbine and dual pressure SRC system enables a 11.6% increase of the engine efficiency at full load. The results presented by Ma et al [3] indicated an engine efficiency increase from 48.5% to 53.8% when installing a single pressure SRC unit in combination with a power turbine unit. Benvenuto et al [4] suggested an alternative design of the dual pressure SRC unit and demonstrated 34% higher electricity generation at design (SRC stand-alone unit) compared to the dual pressure SRC system design typically used in industry.…”
Section: Introductionmentioning
confidence: 98%